1981
DOI: 10.3109/03008208109152128
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Autologous Fat Grafts in Humans and in Mice

Abstract: Autologous fat grafts have been used in a number of surgical procedures, yet properties of fat as a transplant material have remained unclear. This study was designed to compare experimental observations of subcutaneous fat grafts in mice with clinical observations of autologous fat grafts placed over the dura following laminectomy in humans. Subcutaneous fat grafts were observed daily in 75 CFl mice with the use of modified Algire back chambers. Grafts were examined histologically and histochemically at inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…There are several studies which focus on the fate of suctioned versus surgically removed adipose tissue after reimplantation for soft-tissue reconstruction [Watson, 1959;Saunders et al, 1981;Bircoll and Novack, 1987;Matsudo and Toledo, 1988;Nguyen et al, 1990]. Although surgically excised fat maintains its volume slightly better than suction-assisted fat grafts [Kononas et al, 1993], both suctioned and excised tissue undergo significant volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies which focus on the fate of suctioned versus surgically removed adipose tissue after reimplantation for soft-tissue reconstruction [Watson, 1959;Saunders et al, 1981;Bircoll and Novack, 1987;Matsudo and Toledo, 1988;Nguyen et al, 1990]. Although surgically excised fat maintains its volume slightly better than suction-assisted fat grafts [Kononas et al, 1993], both suctioned and excised tissue undergo significant volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of adequate blood supply is thought to be the main cause for this progressive resorption of adipose tissue constructs. 7,[11][12][13] Recently, several groups have demonstrated that the ASC fraction of human adipose tissue is able to secrete numerous factors involved in new blood vessel formation. [14][15][16][17] In vitro adipogenic differentiation of these cells before implantation may influence their angiogenic activity as shown for the murine 3T3-F442A cell line, 18,19 and subsequently affect their ability to stimulate blood vessel ingrowth in tissueengineered constructs.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological and clinical behaviour of fat grafts was well studied by Peer (1956) and reviewed by . It should be pointed out that fat autografts vascularize from the fourth day, an inflammatory reaction with macrophages reaches a peak at 2 months and decreases up to 8 months, normal adipose tissue is present 1-2 years later, surrounded by a thick fibrosis but there is no replacement with scar tissue, some fat resorption usually occurs within 1 year and varies from 30-60 % in patients followed up for 1-3 Years in accordance with Peer (1956), Sokolova (1972), Saunders et al (1981), Illouz (1985;), Chajchir et al (1990, Antoine (1990), Horl et al (1991). However, because of this reduced survival, the fat graft was neglected and the method replaced, by the use of silicone and other alloplastic materials, promoted as modern inert implants for recontouring (Kiskadden and McGregor, 1946;Ashley et al, 1965;Pearl et al, 1978;Franz et al, 1988;Nerobyeyev et al, 1990).…”
Section: Introductionmentioning
confidence: 83%